The Pathophysiological Associations Between Obesity, NAFLD, and Atherosclerotic Cardiovascular Diseases - Li, Meng; Cui, Man; Li, Guoxia; Liu, Yueqiu; Xu, Yunsheng; Eftekhar, Seyed Parsa; Ala, Moein (Hormone and Metabolic Research, 2024)
Obesity, non-alcoholic fatty liver disease (NAFLD), and atherosclerotic cardiovascular diseases are common and growing public health concerns. Previous epidemiological studies unfolded the robust correlation between obesity, NAFLD, and atherosclerotic cardiovascular diseases. Obesity is a well-known risk factor for NAFLD, and both of them can markedly increase the odds of atherosclerotic cardiovascular diseases. On the other hand, significant weight loss achieved by lifestyle modification, bariatric surgery, or medications, such as semaglutide, can concomitantly improve NAFLD and atherosclerotic cardiovascular diseases. Therefore, certain pathophysiological links are involved in the development of NAFLD in obesity, and atherosclerotic cardiovascular diseases in obesity and NAFLD. Moreover, recent studies indicated that simultaneously targeting several mechanisms by tirzepatide and retatrutide leads to greater weight loss and markedly improves the complications of metabolic syndrome. These findings remind the importance of a mechanistic viewpoint for breaking the association between obesity, NAFLD, and atherosclerotic cardiovascular diseases. In this review article, we mainly focus on shared pathophysiological mechanisms, including insulin resistance, dyslipidemia, GLP1 signaling, inflammation, oxidative stress, mitochondrial dysfunction, gut dysbiosis, renin-angiotensin-aldosterone system (RAAS) overactivity, and endothelial dysfunction. Most of these pathophysiological alterations are primarily initiated by obesity. The development of NAFLD further exacerbates these molecular and cellular alterations, leading to atherosclerotic cardiovascular disease development or progression as the final manifestation of molecular perturbation. A better insight into these mechanisms makes it feasible to develop new multi-target approaches to simultaneously unhinge the deleterious chain of events linking obesity and NAFLD to atherosclerotic cardiovascular diseases.
Keywords: obesity; cardiovascular diseases; insulin resistance; endothelial dysfunction; GLP1 signaling